2022
DOI: 10.1038/s41539-021-00119-2
|View full text |Cite
|
Sign up to set email alerts
|

Targeted memory reactivation of face-name learning depends on ample and undisturbed slow-wave sleep

Abstract: Face memory, including the ability to recall a person’s name, is of major importance in social contexts. Like many other memory functions, it may rely on sleep. We investigated whether targeted memory reactivation during sleep could improve associative and perceptual aspects of face memory. Participants studied 80 face-name pairs, and then a subset of spoken names with associated background music was presented unobtrusively during a daytime nap. This manipulation preferentially improved name recall and face re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 21 publications
2
17
0
Order By: Relevance
“…We demonstrated that the TMR procedure at home can yield the typical effect observed in the laboratory, where TMR with quiet sounds improves performance in a spatial memory task (Antony et al, 2018;Creery et al, 2015;Rudoy et al, 2009;Schechtman et al, 2021;Vargas et al, 2019). We also found that loud cues reversed the TMR effect, consistent with our prior findings in a study of face-name learning (Whitmore & Paller, 2022). Accordingly, our findings suggest that home TMR can be useful for investigating memory and perhaps in clinical applications as well.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…We demonstrated that the TMR procedure at home can yield the typical effect observed in the laboratory, where TMR with quiet sounds improves performance in a spatial memory task (Antony et al, 2018;Creery et al, 2015;Rudoy et al, 2009;Schechtman et al, 2021;Vargas et al, 2019). We also found that loud cues reversed the TMR effect, consistent with our prior findings in a study of face-name learning (Whitmore & Paller, 2022). Accordingly, our findings suggest that home TMR can be useful for investigating memory and perhaps in clinical applications as well.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, deliberately disrupting sleep with loud sound cues reverses the TMR effect on spatial recall, selectively weakening reactivated memories (Whitmore & Paller, 2022). Therefore, we suggest that brain-state independent TMR may tend to be ineffective because the intensity and timing of cues cannot be flexibly adjusted to avoid disrupting sleep.…”
Section: Previous Research On Tmr Outside Of the Sleep Laboratorymentioning
confidence: 85%
See 2 more Smart Citations
“…For example, sleep "inertia" typical of early mornings and marked by impaired performance, reduced vigilance, and a desire to return to sleep, is worse when awakened from NREM versus REM sleep (Burke et al, 2015;Scheer et al, 2008;Trotti, 2017). NREM-SWA enhancement has led to improvements in memory consolidation (Bellesi et al, 2014;Diep et al, 2019;Leminen et al, 2017;Papalambros et al, 2017;Tononi et al, 2010) and sustained attention (Krugliakova et al, 2022), consistent with observational study analytics that positively correlate the amount of NREM to the degree of learning and memory performance in both overnight sleep episodes and naps (Alger et al, 2012;Niknazar et al, 2022;Schabus et al, 2005;Whitmore et al, 2022). In fact, SWA may not only be use-dependent, but have localized effects ("local sleep") on involved brain regions following motor and memory tasks (Geva-Sagiv & Nir, 2019; and in rodents Vyazovskiy et al, 2006).…”
Section: Box 1 the Evolving Definition Of Sleep From Behavior To Phys...mentioning
confidence: 69%